THE COVID-19 CRISIS, RISK COMPLIANCE AND ITS AFTERMATH ON PROFESSIONAL ACCOUNTANTS - Emmanuel John Kaka (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2020)
The accounting profession has always assisted to support and shape private and public businesses. But the fast pace at which the outbreak of covid-19 crisis has broad changes in the use of digital technology in businesses, post a great challenges to the accountants and their firms. To overcome the risk and challenges, accountants must add value by embracing digital technology to meet the current and future challenges. The paper is aim at exposing accountants to the risk compliance and aftermath of covid-19 in the way they deliver their services. The method used in data collection was secondary sources. Areas trashed by the paper includes risk and compliance challenge, risk management to be considered during crisis, the need for effective crisis management by the accountant, accountants toolkit for managing covid-19,and technology a must have. The study concludes that digital technology is a must have for professional accountants if really they want to be relevant and stay in business in this period of pandemic and in the future.